For-profit growth and academic decline: a retrospective nationwide assessment of Brazilian medical schools - Andrade, Bruno B.; Villalva-Serra, Klauss; Menezes, Rodrigo C.; Quintanilha, Luiz F.; Avena, Katia de Miranda (Frontiers in Medicine, 2025)
BackgroundThe rapid and predominantly for-profit expansion of medical schools in Brazil over the past decade has raised widespread concerns about the erosion of academic standards in medical education.MethodsThis nationwide, retrospective study analyzed academic performance indicators from all Brazilian medical schools participating in the 2013, 2016, 2019, and 2023 cycles of the National Student Performance Exam (Exame Nacional de Desempenho dos Estudantes - ENADE), a standardized national exam used to assess students’ knowledge at the end of undergraduate programs. We also included the Indicator of Difference between Observed and Expected Performance (Indicador de Diferença entre os Desempenhos Observado e Esperado; IDD), which estimates the value added by institutions by comparing student performance at graduation with their academic background at entry. Data were sourced from publicly available datasets provided by the Brazilian Ministry of Education. We compared trends across public, non-profit private, and for-profit private institutions, using descriptive statistics, non-parametric tests, correlation analysis, and Bayesian mixed-effects regression models to assess the impact of institutional category and class size on academic performance.ResultsThe number of for-profit medical schools in Brazil nearly doubled between 2013 and 2023. These institutions consistently demonstrated lower ENADE scores compared to public and non-profit peers. Although IDD scores showed some early gains, they declined significantly in 2023, particularly among new medical schools taking the ENADE for the first time, most of which were for-profit. Larger class sizes were negatively correlated with both ENADE and IDD scores. Regression models showed that public institutions outperformed for-profit schools by an average margin of more than 21 ENADE points, while class size emerged as a modest but statistically significant negative predictor of IDD.ConclusionOur findings reveal that the unregulated expansion of for-profit medical schools in Brazil has been accompanied by a decline in academic performance, as measured by national benchmarks. These patterns suggest a structural misalignment between the commercial logic of expansion and the core educational mission of medical training. Regulatory reforms are urgently needed to realign the growth of medical education with principles of academic quality and social accountability.